CRITICAL REVIEW OF HEALTH SERVICES AND HOSPITALS MANAGEMENT SOFTWARE SYSTEMS IN ASSESSING INTEGRATION CAPABILITIES, USER INTERFACE DESIGN, AND IMPACT ON OPERATIONAL EFFICIENCY - MAHDI MOHAMMAD M ALMOSED, MOHAMMED SALEM HUSSAIAN ALYAMI, RASHED MOHAMMED A AL SHARYAH, ABDULLAH HASSAN ABDULLAH ALYAMI, MOHAMMED MAHDI ALMUHAMIDH, MAHDI SALEM HUSSEIN ALYAMI, MOHAMMED AHMED SAUD AL ABBAS, MOHAMMED HUSSAIN NASSER ALYAMI, (Chelonian Research Foundation, 2022)
Software systems Health services and hospital management contribute considerably to the effective delivery of modern healthcare by facilitating the administration of patient information, scheduling, billing, and other tasks of doctors and managers. It, however, conducts critical and evaluative evaluations on the integration, user interface, and efficiency of such software systems. In the literature review, updated with current data and empirical studies, this study analyzes how this health services and hospital management software currently functions, what its strengths and limitations are, and develops recommendations for how it can be further improved in healthcare settings. This research shows that successful implementation requires no-break integration, a user-friendly interface, and identifying ways to boost operation efficiency through the right software design. Keywords: health service, hospital, management software systems, integration, user interface design, operational effectiveness.